Tolaki Tribe's Marriage: The Struggle of Islamic Law and Customary Law - Ipandang, Ipandang; Yuliyanti, Ai Yeni (Madania: Jurnal Kajian Keislaman, 2020)
This study aims to understand the history and struggles of Islamic law and Tolaki culture in the Munakahat Fiqh, inherited from the Tolaki community as contained in the Tolaki customary law structure. This study uses a qualitative descriptive method and a phenomenological approach. This research shows that the struggle of Islamic law and marriage culture in the Tolaki community is that the relationship between Islam and Tolaki culture shows adaptation, mutual understanding, and conversation. This relationship means no dominant or mutually dominant camps in this cycle of marriage, Islam, and traditions. Thus, there is a need for the role of traditional leaders, religious leaders, community leaders, and the government to socialize intensely the importance of cultural values in society, nation, and state to preserve existing culture for the continuity of future generations in various activities. Penelitian ini bertujuan untuk memahami sejarah dan pergumulan tentang hukum Islam dan budaya Tolaki dalam fikih munakahat yang diwariskan kepada masyarakat Tolaki yang terdapat dalam struktur hukum adat Tolaki. Dengan menggunakan metode deskriptif kualitatif dan pendekatan fenomenologi, Hasil penelitian menunjukkan bahwa pergumulan hukum islam dan budaya perkawinan pada masyarakat Tolaki adalah hubungan antara Islam dan budaya Tolaki menunjukkan adaptasi, saling pengertian dan percakapan satu sama lain. Artinya, tidak ada kubu yang dominan atau yang saling dominan dalam siklus pernikahan, Islam, dan tradisi ini. Untuk itulah perlunya peranan tokoh adat, tokoh agama, tokoh masyarakat maupun pemerintah secara intens dan berkelanjutan dilaksanakan berbagai kegiatan yang mensosialisasikan pentingnya nilai-nilai budaya dalam kehidupan bermasyarakat, berbangsa dan bernegara guna melestarikan budaya yang sudah ada demi kelangsungan generasi mendatang.